Descent and spatial distribution of eleven strains of Aedes aegypti resistant to organophosphates and carbamates in Sullana, Peru, 2024 (Revista Médica de Trujillo, 2026)
Objective: To determine the inheritance and spatial distribution of resistance to organophosphates and carbamates in eleven Aedes aegypti strains from Sullana, Peru, 2024. Materials and Methods: Under laboratory conditions, L4-stage larvae were reared to adulthood, representing an F0 generation for each strain. Subsequently, adults were allowed to reproduce to obtain F1 eggs. From each F0 strain, ten adult females were selected and distributed into eleven groups, yielding a total of 110 females. Likewise, from each F1 strain, sixty eggs were selected and distributed into eleven groups, for a total of 660 eggs. DNA was extracted from the legs of each group of females and from the eggs, and the AceR gene (acetylcholinesterase mutation, AChE) was detected using conventional PCR. Results: The AceR gene was identified in all strains, both in F0 females and F1 eggs, suggesting that this mutation represents a transmissible and/or heritable genetic trait. In addition, the spatial distribution of mutant mosquitoes included a cemetery, which may represent one of the foci contributing to the spread of Aedes aegypti carrying the AceR mutation. Conclusion: These findings demonstrate the circulation and establishment of Aedes aegypti populations with a genotype resistant to organophosphate and carbamate insecticides, providing valuable entomological and genetic information for the development of phenotypic resistance assays and/or effective vector control strategies.